Synthesis of sp3-rich chemical libraries based upon 1, 2-diazetidines. (22nd January 2021) - Dean, Conor; Roesner, Stefan; Rajkumar, Sundaram; Clarkson, Guy J.; Jones, Matthew; Shipman, Michael
Abstract: A strategy for the creation of sp 3 -rich, non-planar scaffolds for drug discovery is described. Stereocontrolled ring opening of homochiral 1, 2-epoxides by hydrazine monohydrate followed by selective protection of both nitrogen atoms and Mitsunobu ring closure gives differentially protected, enantiomerically pure 1, 2-diazetidines (up to 98% ee) bearing a variety of C-3 substituents. Iterative C–N functionalization at the two nitrogen atoms using a range of chemistries and coupling partners produces a 1, 2-diazetidine based chemical library. Crystallographic data confirm that these frameworks display significant sp 3 -character with the nitrogen substituents adopting an anti -configuration. Graphical abstract: Image 1